Active material composite and secondary battery
By incorporating a phosphoric acid compound and C-F elements in the coating layer of active material complexes, the issue of increased resistance after cycling tests is addressed, resulting in enhanced durability and stability.
Patent Information
- Application Number
- JP2023031327
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-03-01
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-03-01
AI Technical Summary
Conventional active material complexes exhibit significant increases in resistance after cycling tests, indicating a need for improved durability and stability.
The development of an active material complex comprising active material particles coated with a layer containing a phosphoric acid compound and elements C and F, which enhances the durability of the coating layer and the overall active material composite.
The active material complexes with a phosphoric acid compound and C-F containing coating layers demonstrate a minimal increase in resistance after cycling tests, showcasing improved durability and stability compared to conventional materials.
Smart Images

Figure 0007658388000002 
Figure 0007658388000003 
Figure 0007658388000004
Abstract
Description
[Technical field]
[0001] The present application discloses an active material composite and a secondary battery. [Background technology]
[0002] A technique for forming a coating layer on the surface of an active material particle to obtain an active material composite is known. For example, Patent Document 1 discloses a positive electrode active material material having a strongly basic positive electrode active material and a coating layer that covers the surface of the positive electrode active material and has a polyanion structure part that exhibits acidity. Patent Document 2 discloses a technique for introducing a halogen when coating the surface of a lithium-containing composite oxide particle with a compound containing Li, A, and O (A is one or more elements selected from the group consisting of Ti, Zr, Ta, Nb, Zn, W, and Al). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2012-099323 A [Patent Document 2] International Publication No. 2019 / 035418 Summary of the Invention [Problem to be solved by the invention]
[0004] Conventional active material composites have room for improvement in terms of the rate of increase in resistance after a cycle test. [Means for solving the problem]
[0005] The present application discloses the following aspects as means for solving the above problems. <Aspect 1> An active material composite having active material particles and a coating layer, the coating layer covers at least a part of the surface of the active material particle, the coating layer contains a phosphate compound, The elements constituting the coating layer include C and F. Active material complex. <Aspect 2> 2. The active material composite of Embodiment 1, The phosphate compound contains one or both of Li and B. Active material complex. <Aspect 3> The active material composite of Aspect 1 or 2, The coating layer has a C-F bond. Active material complex. <Aspect 4> The active material composite according to any one of Aspects 1 to 3, The coating layer contains NaF. Active material complex. <Aspect 5> A secondary battery having a positive electrode active material layer, an electrolyte layer, and a negative electrode active material layer, The positive electrode active material layer includes the active material composite according to any one of aspects 1 to 4. Secondary battery. Effect of the Invention
[0006] The active material composite of the present disclosure has a small rate of increase in resistance after a cycle test. [Brief description of the drawings]
[0007] [Figure 1] 2 shows a schematic diagram of an example of a cross-sectional shape of an active material composite. [Figure 2A] 1 shows an example of a flow of a manufacturing method (first embodiment) of an active material composite. [Figure 2B] 1 shows an example of a flow of a manufacturing method (first embodiment) of an active material composite. [Figure 3A] 1 shows an example of the flow of a method for producing an active material composite (second embodiment). [Figure 3B] 1 shows an example of the flow of a method for producing an active material composite (second embodiment). [Figure 4] 1 illustrates an example of the configuration of a secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] 1.Active material composite Fig. 1 shows a schematic cross-sectional structure of an active material composite according to one embodiment. As shown in Fig. 1, the active material composite 1 has an active material particle 1a and a coating layer 1b. The coating layer 1b coats at least a part of the surface of the active material particle 1a. The coating layer 1b contains a phosphate compound. Elements constituting the coating layer 1b include C and F.
[0009] 1.1 Active material particles The active material particles 1a may be positive electrode active material particles or negative electrode active material particles. In particular, when the active material particles 1a are positive electrode active material particles, a higher effect is likely to be exhibited.
[0010] 1.1.1 Active material The active material constituting the active material particles 1a may be at least one selected from, for example, lithium-containing compounds; sulfur-based active materials such as elemental sulfur and sulfur compounds; Si-based active materials such as Si and Si alloys; carbon-based active materials such as graphite and hard carbon; metallic lithium and lithium alloys; etc. In particular, when the active material particles 1a contain a lithium-containing compound, a higher effect is likely to be obtained. Only one type of active material may be used alone, or two or more types may be used in combination.
[0011] The lithium-containing compound as the active material may be a lithium-containing oxide containing at least one element M, Li, and O. The element M may be, for example, at least one selected from Mn, Ni, Co, Al, Mg, Ca, Sc, V, Cr, Cu, Zn, Ga, Ge, Y, Zr, Sn, Sb, W, Pb, Bi, Fe, and Ti, or at least one selected from the group consisting of Mn, Ni, Co, Al, Fe, and Ti. More specifically, the lithium-containing oxide may be lithium cobalt oxide, lithium nickel oxide, lithium manganate, lithium nickel cobalt oxide, lithium nickel manganate, lithium cobalt manganate, lithium nickel cobalt manganate (Li1±α Ni x Co y Mn z O 2±δ (For example, 0 < x < 1, 0 < y < 1, 0 < z < 1, x + y + z = 1)), spinel-type lithium compounds (Li 1+x Mn 2-x-y M y O4 (M is one or more selected from Al, Mg, Co, Fe, Ni, and Zn), such as hetero-element substituted Li-Mn spinel with a composition represented by etc.), lithium nickel cobalt aluminate (for example, Li 1±α Ni p Co q Al r O 2±δ (For example, p + q + r = 1)), lithium titanate, lithium metal phosphate (such as LiMPO4, etc., M is one or more selected from Fe, Mn, Co, and Ni), etc. may be at least one selected. In particular, when the active material particles contain a lithium-containing oxide containing at least one of Ni, Co, and Mn as constituent elements, together with Li and O, higher performance is more easily obtained. Alternatively, when the active material particles contain a lithium-containing oxide containing at least one of Ni, Co, and Al as constituent elements, together with Li and O, higher performance is also more easily obtained.
[0012] 1.1.2 Particle Shape The active material particles may be solid particles, hollow particles, or particles having voids. The active material particles may be primary particles or secondary particles formed by aggregation of a plurality of primary particles. The average particle diameter (D50) of the active material particles may be, for example, 1 nm or more and 500 μm or less. The lower limit may be 5 nm or more or 10 nm or more, and the upper limit may be 100 μm or less, 50 μm or less, or 30 μm or less. In the present application, the average particle diameter D50 is the particle diameter (median diameter) at the integrated value 50% in the volume-based particle size distribution determined by the laser diffraction / scattering method.
[0013] 1.2 Coating Layer The coating layer 1b covers at least a part of the surface of the active material particle 1a. By covering at least a part of the surface of the active material particle 1a with the coating layer 1b, adverse chemical reactions at the interface between the active material composite 1 and other materials (for example, a sulfide solid electrolyte) are less likely to occur, and deterioration of the active material composite 1 is suppressed.
[0014] 1.2.1 Components contained in coating layer 1b: Phosphate compound The coating layer 1b contains a phosphate compound. The phosphate compound is a compound containing P and O. The phosphate compound contained in the coating layer 1b may contain, for example, one or both of Li and B. That is, the phosphate compound may be, for example, a compound containing Li, P, and O, a compound containing B, P, and O, or a compound containing Li, B, P, and O. When the phosphate compound contained in the coating layer 1b contains one or both of Li and B, the active material complex 1 has even better durability. Whether the coating layer 1b contains a phosphate compound can be confirmed by, for example, XPS, SEM-EDX, or the like. For example, when the surface of the active material complex 1 is analyzed by XPS, a peak derived from P or O may be confirmed. Alternatively, when the surface of the active material complex 1 is analyzed by elemental analysis by SEM-EDX, or the like, P or O may be confirmed.
[0015] 1.2.2 Other constituent elements contained in coating layer 1b: C and F The coating layer 1b contains C and F as constituent elements. C and F may or may not be chemically bonded to each other. In addition, C and F may be included in the form of a compound. According to the findings of the present inventors, when the coating layer 1b contains C and F together with the above-mentioned phosphate compound, the coating layer 1b is less likely to decompose even at a high potential, and the durability of the coating layer 1b is improved. Whether the elements constituting the coating layer 1b contain C and F can be confirmed by, for example, XPS, SEM-EDX, or the like. For example, the active material complex 1 may be one in which a peak derived from C or F is confirmed when its surface is analyzed by XPS. Alternatively, the active material complex 1 may be one in which C or F is confirmed when its surface is analyzed by elemental analysis by SEM-EDX, or the like.
[0016] The coating layer 1b may have a C—F bond. This makes it easier to further improve the durability of the coating layer 1b. Whether the coating layer 1b has a C—F bond or not can be confirmed by, for example, X-ray photoelectron spectroscopy (XPS). For example, when the surface of the active material composite 1 is analyzed by XPS, it is found that the coating layer 1b has a C—F bond. x A peak derived from may be confirmed.
[0017] 1.2.3 C and F sources The constituent elements C and F contained in the coating layer 1b may be derived from a fluoro compound. For example, the constituent elements C and F contained in the coating layer 1b may be derived from perfluoropolyether (PFPE). Perfluoropolyether has an ether bond, and is therefore considered to have a high affinity for the active material particles 1a and the coating layer 1b. In addition, perfluoropolyether is considered to have a low reactivity with other materials (e.g., sulfide solid electrolyte). In this regard, when the constituent elements C and F contained in the coating layer 1b are derived from perfluoropolyether, a higher effect is likely to be obtained.
[0018] The perfluoropolyether has a perfluoropolyether chain. For example, the perfluoropolyether may be represented by the following formula (1). E1-Rf1-R F -O-Rf2-E2(1) [In formula (1), Rf1 and Rf2 each independently represent a C1-16 divalent alkylene group optionally substituted by one or more fluorine atoms, E1 and E2 are each independently a monovalent group selected from the group consisting of a fluorine group, a hydrogen group, a hydroxyl group, an aldehyde group, a carboxylic acid group, a C1-10 alkyl ester group, an amide group which may have one or more substituents, and an amino group which may have one or more substituents; R F is a divalent fluoropolyether group.
[0019] In the above formula (1), Rf1 and Rf2 are each independently a C1-16 divalent alkylene group optionally substituted with one or more fluorine atoms. In one embodiment, the "C1-16 divalent alkylene group" in the C1-16 divalent alkylene group optionally substituted with one or more fluorine atoms may be linear or branched, preferably a linear or branched C1-6 alkyl alkylene group, particularly a C1-3 alkylene group, more preferably a linear C1-6 alkylene group, particularly a C1-3 alkylene group. In one embodiment, the "C1-16 divalent alkylene" in the C1-16 divalent alkylene group optionally substituted by one or more fluorine atoms may be linear or branched, and is preferably a linear or branched C1-6 fluoroalkylene group, in particular a C1-3 fluoroalkylene group, specifically -CF2CH2- and -CF2CF2CH2-, and more preferably a linear C1-6 perfluoroalkylene group, in particular a C1-3 perfluoroalkylene group, specifically a group selected from the group consisting of -CF2-, -CF2CF2- and -CF2CF2CF2-.
[0020] In the above formula (1), E1 and E2 are each independently a monovalent group selected from the group consisting of a fluorine group, a hydrogen group, a hydroxyl group, an aldehyde group, a carboxylic acid group, a C1-10 alkyl ester group, an amide group which may have one or more substituents, and an amino group which may have one or more substituents. As described above, perfluoropolyether has low reactivity with the sulfide solid electrolyte described below. Therefore, even when perfluoropolyether comes into contact with a sulfide solid electrolyte, the ion conductivity is unlikely to decrease due to alteration or deterioration of the sulfide solid electrolyte. In particular, when the perfluoropolyether has a non-polar group as an end group, the reaction between the perfluoropolyether and the sulfide solid electrolyte is further suppressed, and even higher effects can be expected. In this regard, the above E1 and E2 are each independently preferably a fluorine group. In one embodiment, E1-Rf1 and E2-Rf2 may each independently be a group selected from the group consisting of -CF3, -CF2CF3, and -CF2CF2CF3.
[0021] In the above formula (1), R F R is independently at each occurrence a divalent fluoropolyether group. F is preferably represented by formula (2): -(OC6F 12 ) a -(OC5F 10 ) b -(OC4F8) c -(OC3R Fa 6) d -(OC2F4) e -(OCF2) f - (2) [In formula (2): R Fa is independently at each occurrence a hydrogen atom, a fluorine atom, or a chlorine atom; a, b, c, d, e, and f each independently represent an integer of 0 to 200; the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of occurrence of each repeating unit enclosed in parentheses with a, b, c, d, e, or f in the formula is arbitrary. However, all R Fa is a hydrogen atom or a chlorine atom, at least one of a, b, c, e and f is 1 or greater.] R is a group represented by the formula: Fa is preferably a hydrogen atom or a fluorine atom, more preferably a fluorine atom. a, b, c, d, e and f may each independently be an integer of 0 to 100. The sum of a, b, c, d, e and f is preferably 5 or more, more preferably 10 or more, for example 15 or more or 20 or more. The sum of a, b, c, d, e and f is preferably 200 or less, more preferably 100 or less, further preferably 60 or less, for example 50 or less or 30 or less.
[0022] These repeating units may be linear or branched. F In the formula, the ratio of d to f (hereinafter referred to as "d / f ratio") may be 0.5 to 4, preferably 0.6 to 3, more preferably 0.7 to 2, and even more preferably 0.8 to 1.4. By making the d / f ratio 4 or less, the lubricity and chemical stability are further improved. The smaller the d / f ratio, the more the lubricity is improved. On the other hand, by making the d / f ratio 0.5 or more, the stability of the compound can be further increased. The larger the d / f ratio, the more the stability of the fluoropolyether structure is improved. In this case, the value of f is preferably 0.8 or more. In the above, R F The number average molecular weight of the portion is not particularly limited, but is, for example, 500 to 30,000, preferably 1,500 to 30,000, and more preferably 2,000 to 10,000. F The number average molecular weight of 19 This is a value measured by F-NMR.
[0023] 1.2.4 Element ratio By having the coating layer 1b, the active material composite 1 can have, for example, the following configuration. That is, the element ratio Li / P of Li to P when the surface of the active material composite 1 is analyzed by XPS may be, for example, 0 to 1.40, 0.80 to 1.40, or 0.90 to 1.30. The element ratio B / P of B to P when the surface of the active material composite 1 is analyzed by XPS may be, for example, 0 to 10, or 0 to 1. The element ratio F / P of F to P when the surface of the active material composite 1 is analyzed by XPS may be, for example, 0.05 to 2.00, or 0.10 to 1.60.
[0024] 1.2.5 Coverage The coverage of the coating layer 1b on the surface of the active material particle 1a is not particularly limited. The coating layer 1b may cover 70% to 100%, 90% to 100%, or 95% to 100% of the surface of the active material particle 1a. The coverage (area ratio) of the coating layer 1b on the surface of the active material particle 1a can be calculated by observing a scanning electron microscope (SEM) image of the cross section of the active material composite. Alternatively, it can be calculated by calculating the element ratio of the surface by X-ray photoelectron spectroscopy (XPS).
[0025] 1.2.6 Thickness The thickness of the coating layer 1b is not particularly limited, and may be, for example, 0.1 nm or more and 500 nm or less. The lower limit may be 0.5 nm or more, 1 nm or more, or 10 nm or more, and the upper limit may be 300 nm or less, 100 nm or less, 50 nm or less, or 30 nm or less. The thickness of the coating layer 1b on the surface of the active material particle 1a can be specified, for example, by observing the cross section of the active material composite with a scanning electron microscope (SEM) or the like.
[0026] 1.2.7 Other The above-mentioned constituent elements C and F may be present inside the coating layer 1b, may be present on the surface of the coating layer 1b, or may be present both inside and on the surface of the coating layer 1b. In particular, when the coating layer 1b contains C and F as constituent elements at least inside, higher performance is likely to be obtained. Furthermore, the coating layer 1b may contain impurities derived from the raw material. For example, the coating layer 1b may contain Na as a constituent element. Na may be contained in phosphoric acid as an excipient. Furthermore, Na may react with the above-mentioned F. That is, the coating layer 1b may contain NaF.
[0027] 2. Method for producing active material composite The active material composite 1 of the present disclosure can be produced, for example, by contacting the surface of the active material particle 1a with a predetermined coating liquid, followed by drying, etc. For example, the method is as shown in the first or second embodiment below. Note that, although the following description illustrates a method of air-drying the slurry droplets, the active material composite of the present disclosure can also be produced by other methods.
[0028] 2.1 First form As shown in FIGS. 2A and 2B , the method for producing an active material composite according to the first embodiment includes the following steps: Step S1-1: forming a slurry 1c containing active material particles 1a and a coating liquid 1bx into droplets to obtain slurry droplets 1d; and Step S1-2: drying the slurry droplets 1d with a gas flow in a heated gas to form a coating layer 1b on the surface of the active material particles 1a, thereby obtaining an active material composite 1; Here, the coating solution 1bx used in the first embodiment may contain a phosphoric acid compound and may also contain a C and F source.
[0029] 2.1.1 Process S1-1 In step S1-1, the slurry 1c containing the active material particles 1a and the coating liquid 1bx is turned into droplets to obtain the slurry droplets 1d. The "slurry" refers to a suspension or a suspension containing the active material particles 1a and the coating liquid 1bx, and may have a degree of fluidity that allows it to be turned into droplets. The active material particles 1a contained in the slurry are as described above. The coating liquid 1bx constituting the slurry contains, for example, a phosphoric acid compound and a C and F source. The phosphoric acid compound may be, for example, a compound containing Li, P, and O, as described above, or a compound containing B, P, and O, or a compound containing Li, B, P, and O. The C and F sources may be, for example, a compound such as perfluoropolyether, as described above. The concentrations of the phosphoric acid compound and the C and F sources contained in the coating liquid 1bx are not particularly limited, and may be appropriately adjusted according to the composition of the intended coating layer 1b. The solvent constituting the coating liquid 1bx may be, for example, water. The solid content concentration of the slurry is not particularly limited. The slurry may contain some solid or liquid components in addition to the above-mentioned active material particles 1a and coating liquid 1bx.
[0030] In step S1-1, the above-mentioned slurry 1c is turned into droplets. The "dropletization" of the slurry means that the slurry 1c containing the active material particles 1a and the coating liquid 1bx is turned into grains containing the active material particles 1a and the coating liquid 1bx. The method of turning the slurry 1c containing the active material particles 1a and the coating liquid 1bx into droplets is not particularly limited. For example, there is a method of turning the slurry 1c into droplets by spraying it. When spraying the slurry 1c, a spray nozzle may be used. Examples of the method of spraying the slurry 1c using a spray nozzle include, but are not limited to, a pressurized nozzle method and a two-fluid nozzle method. Alternatively, the slurry 1c may be turned into droplets using a rotary atomizer.
[0031] By step S1-1, slurry droplets 1d are obtained. The "slurry droplets" are particles of a slurry 1c containing active material particles 1a and a coating liquid 1bx. The number of active material particles 1a contained in the slurry droplets 1d is not particularly limited. The size of the slurry droplets 1d is also not particularly limited. The diameter (sphere equivalent diameter) of the slurry droplets 1d may be, for example, 0.5 μm or more or 5 μm or more, or 5000 μm or less or 1000 μm or less. The diameter of the slurry droplets 1d can be measured, for example, using a two-dimensional image obtained by capturing an image of the slurry droplets 1d, or can be measured using a laser diffraction type particle size distribution meter. Alternatively, the droplet diameter can be estimated from the operating conditions of the device that forms the slurry droplets 1d.
[0032] 2.1.2 Process S1-2 In step S1-2, the slurry droplets 1d are air-dried in a heated gas to form a coating layer 1b on the surface of the active material particles 1a, thereby obtaining the active material composite 1. "Air-drying" means drying the slurry droplets 1d while suspending them in a high-temperature air flow. "Air-drying" can include not only drying but also an accompanying operation using a dynamic air flow. By continuously applying hot air to the slurry droplets 1d by air-drying, a force is continuously applied to the slurry droplets 1d. By utilizing this, for example, step S1-2 may include disintegrating (disintegrating) the aggregates of the slurry droplets 1d (or the aggregates of the active material composite 1) by air-drying. In other words, even if granules of the slurry droplets 1d or the active material composite 1 are generated in step S1-2, the granules can be disintegrated by air-drying. Therefore, a slurry with a low solid content concentration can be used, and the processing speed can be easily increased. In this way, in step S1-2, crushing the slurry droplets 1d etc. by air flow drying makes it easier to shorten the production time and to produce a high-performance active material composite 1. In step S1-2, the drying and crushing may be performed simultaneously or separately. In step S1-2, a first air flow drying in which the drying of the slurry droplets 1d is predominant, and a second air flow drying in which the crushing of the active material composite 1 is predominant may be performed. The second step may also be performed repeatedly.
[0033] In step S1-2, the temperature of the heated gas, the supply amount (flow rate) of the heated gas, the supply rate (flow rate) of the heated gas, and the treatment time (drying time) by the heated gas can be appropriately set in consideration of the size of the device used and the shape of the slurry droplets 1d. For example, conditions such as those disclosed in JP 2022-047501 A may be adopted. In step S1-2, a heated gas that is substantially inert to the active material particles 1a and the coating liquid 1bx may be used. For example, an oxygen-containing gas such as air, an inert gas such as nitrogen or argon, or low dew point dry air may be used. In that case, the dew point may be -10°C or less, -50°C or less, or -70°C or less. As an apparatus for performing the air flow drying, for example, a spray dryer may be used, but is not limited thereto.
[0034] 2.1.3 Other processes After the airflow drying, calcination may be optionally performed. As a calcination device, for example, a muffle furnace, a hot plate, or the like can be used, but is not limited thereto. The calcination conditions are not particularly limited, and can be appropriately set according to the type of active material composite 1.
[0035] 2.2 Second form As shown in FIGS. 3A and 3B , the method for producing an active material composite according to the second embodiment includes the following steps: Step S2-1: forming droplets from a first slurry 1fx containing active material particles 1a and a first coating liquid 1ex to obtain first slurry droplets 1gx; Step S2-2: drying the first slurry droplets 1gx in a heated gas stream to form a first coating layer 1h on the surface of the active material particles 1a to obtain an intermediate composite 1x; Step S2-3: forming droplets of a second slurry 1fy containing the intermediate composite 1x and a second coating liquid 1ey to obtain second slurry droplets 1gy; and Step S2-4: The second slurry droplets 1gy are dried in a heated gas flow to form a coating layer 1b on the surface of the active material particles 1a, thereby obtaining an active material composite 1. Here, the first coating liquid 1ex may contain at least a phosphoric acid compound, but may not contain a C and F source. The second coating liquid 1ey may contain at least a C and F source. The "phosphate compound" and the "C and F source" are as described above.
[0036] In the second embodiment, a first coating layer 1h containing a phosphate compound is formed on the surface of the active material particle 1a to obtain an intermediate composite 1x, and then a second coating layer containing C and F is formed on the intermediate composite 1x (or C and F are introduced into the first coating layer 1h). In the second embodiment, the first coating liquid 1ex and the second coating liquid 1ey are used to form the slurry into droplets and dry the slurry droplets in air in two steps. The conditions for forming the droplets in steps S2-1 and S2-3 and the conditions for drying the slurry in air in steps S2-2 and S2-4 may be the same as those in the first embodiment, except that the types of the coating liquids are different. For example, the conditions disclosed in JP 2022-047501 A may be adopted.
[0037] 3. Secondary battery FIG. 4 shows a schematic configuration of a secondary battery 100 according to an embodiment. As shown in FIG. 4, the secondary battery 100 has a positive electrode active material layer 20, an electrolyte layer 30, and a negative electrode active material layer 40, and the positive electrode active material layer 20 includes the active material composite 1. In addition, the problem related to the durability of the active material composite 1 is more likely to become apparent when the secondary battery 100 includes a solid electrolyte. In this regard, in the secondary battery 100, at least one of the positive electrode active material layer 20, the electrolyte layer 30, and the negative electrode active material layer 40 may include a solid electrolyte. In particular, in the secondary battery 100, when at least the positive electrode active material layer 20 includes an inorganic solid electrolyte, particularly when at least the positive electrode active material layer 20 includes a sulfide solid electrolyte, a higher effect is likely to be obtained. In the secondary battery 100, all of the positive electrode active material layer 20, the electrolyte layer 30, and the negative electrode active material layer 40 may include a sulfide solid electrolyte.
[0038] The sulfide solid electrolyte may be a glass-based sulfide solid electrolyte (sulfide glass), a glass-ceramic-based sulfide solid electrolyte, or a crystalline sulfide solid electrolyte. When the sulfide solid electrolyte has a crystalline phase, examples of the crystalline phase include a Thio-LISICON type crystalline phase, an LGPS type crystalline phase, and an argyrodite type crystalline phase. The sulfide solid electrolyte may contain, for example, Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, In), and S element. Further, the sulfide solid electrolyte may further contain at least one of O element and halogen element. Also, the sulfide solid electrolyte may contain S element as the main component of the anion element. The composition of the sulfide solid electrolyte is not particularly limited, and examples include xLi2S·(100-x)P2S5 (70≦x≦80), yLiI·zLiBr·(100-y-z)(xLi2S·(1-x)P2S5) (0.7≦x≦0.8, 0≦y≦30, 0≦z≦30), etc. Alternatively, the sulfide solid electrolyte may have a composition represented by the general formula: Li 4-x Ge 1-x P x S4 (0<x<1). In the above general formula, at least a part of Ge may be substituted with at least one of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. In the above general formula, at least a part of P may be substituted with at least one of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. In the above general formula, a part of Li may be substituted with at least one of Na, K, Mg, Ca, and Zn. In the above general formula, a part of S may be substituted with a halogen (at least one of F, Cl, Br, and I). Alternatively, the sulfide solid electrolyte may be Li 7-a PS 6-a X a(X is at least one of Cl, Br, and I, and a is a number of 0 or more and 2 or less). a may be 0 or more than 0. In the latter case, a may be 0.1 or more, 0.5 or more, or 1 or more. Also, a may be 1.8 or less, or 1.5 or less.
[0039] The secondary battery 100 may be a solid-state battery. A solid-state battery refers to a battery in which an electrolyte having carrier ion conductivity is mainly composed of a solid electrolyte. However, a liquid component may be included in part. Alternatively, the secondary battery 100 may be an all-solid-state battery that does not substantially include a liquid component. In addition, as shown in FIG. 4, the secondary battery 100 may include a positive electrode current collector 10 in contact with the positive electrode active material layer 20. In addition, the secondary battery 100 may include a negative electrode current collector 50 in contact with the negative electrode active material layer 40. The secondary battery 100 may be manufactured by, for example, a method such as that disclosed in JP 2022-047501 A, except that the positive electrode active material layer 20 includes the above-mentioned active material composite 1. EXAMPLES
[0040] The technology of the present disclosure will be described in more detail below with reference to examples, but the technology of the present disclosure is not limited to the following examples.
[0041] 1. Preparation of Coating Solution 1.1 Comparative Example 1 Metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) 10.8 g was dissolved in ion-exchanged water 166.0 g. Lithium hydroxide monohydrate was then added so that the Li / P (molar ratio) was 0.45, thereby obtaining a coating solution according to Comparative Example 1.
[0042] 1.2 Example 1 10.8 g of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 166.0 g of ion-exchanged water. Then, lithium hydroxide monohydrate was added so that the Li / P (molar ratio) was 0.45 to obtain an aqueous solution. Furthermore, perfluoropolyether (PFPE) was added to the aqueous solution so that the amount was 5 mass % to obtain a coating solution according to Example 1. In this example, the perfluoropolyether has the following chemical structure. R 1 -O(CF2CF2CF2O) n -R 2 Here, R 1 and R 2 are each -CF3.
[0043] 1.3 Example 2 10.8 g of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 166.0 g of ion-exchanged water. Lithium hydroxide monohydrate was then added so that the Li / P (molar ratio) was 0.45 to obtain an aqueous solution. Furthermore, perfluoropolyether was added so that the amount was 10 mass % relative to the aqueous solution to obtain a coating solution according to Example 2.
[0044] 1.4 Comparative Example 2 10.8 g of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 166.0 g of ion-exchanged water. Then, boric acid (manufactured by Nacalai Tesque, Inc.) was added so that the B / P (molar ratio) was 1.00, thereby obtaining a coating solution according to Comparative Example 2.
[0045] 1.5 Example 3 The coating liquid for the first layer (first coating liquid) was the same as that used in Comparative Example 2. The coating liquid for the second layer (second coating liquid) was a liquid in which 0.1 g of perfluoropolyether was dispersed in 10 g of ion-exchanged water.
[0046] 1.6 Example 4 The coating liquid for the first layer (first coating liquid) was the same as that used in Comparative Example 2. The coating liquid for the second layer (second coating liquid) was a liquid in which 0.5 g of perfluoropolyether was dispersed in 10 g of ion-exchanged water.
[0047] 1.7 Example 5 Metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (10.8 g) was dissolved in ion-exchanged water (166.0 g). Then, boric acid (manufactured by Nacalai Tesque, Ltd.) was added so that the B / P (molar ratio) was 1.00 to obtain an aqueous solution. Furthermore, perfluoropolyether was added to the aqueous solution so that the content was 5 mass % to obtain a coating solution according to Example 5.
[0048] 1.8 Comparative Example 3 Metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) 10.8 g was dissolved in ion-exchanged water 166.0 g. Then, boric acid (manufactured by Nacalai Tesque, Inc.) was added so that the B / P (molar ratio) was 1.00. Furthermore, lithium hydroxide monohydrate was added so that the Li / (P+B) (molar ratio) was 0.50, thereby obtaining a coating solution according to Comparative Example 3.
[0049] 1.9 Example 6 The coating liquid of Example 6 was obtained by adding perfluoropolyether to the coating liquid of Comparative Example 3 so that the content was 5 mass %.
[0050] 2. Preparation of active material composite 2.1 Examples 1, 2, 5, 6, Comparative Examples 1, 2, and 3 LiNi as active material particles 1 / 3 Mn 1 / 3 Co 1 / 3 22 g of the above coating liquid was added to 50 g of O2 particles (manufactured by Nichia Corporation) to prepare a slurry. The slurry was fed to a spray dryer (Buchi Mini Spray Dryer B-290) using a liquid pump, and the slurry was turned into droplets (step S1-1) and the slurry droplets were air-dried (step S1-2) to obtain an active material composite. The supply air temperature in the spray dryer was 200°C, and the supply air volume was 0.45 m3 / min, and the liquid delivery rate was 0.5 g / sec.
[0051] 2.2 Examples 3 and 4 LiNi as active material particles 1 / 3 Mn 1 / 3 Co 1 / 3 22 g of the first coating liquid was added to 50 g of O2 particles (manufactured by Nichia Corporation) to prepare a first slurry. The first slurry was fed to a spray dryer (manufactured by Buchi, Mini Spray Dryer B-290) using a liquid pump, and the first slurry was turned into droplets (step S2-1) and the first slurry droplets were air-dried (step S2-2) to obtain an intermediate composite. The supply air temperature in the spray dryer was 200°C, and the supply air volume was 0.45 m 3 / min, and the liquid delivery rate was 0.5 g / sec.
[0052] To 40 g of the intermediate composite, 18 g of the second coating liquid was added to prepare a second slurry. Using a liquid pump, the second slurry was fed to a spray dryer (Buchi Mini Spray Dryer B-290), where the second slurry was turned into droplets (step S2-3) and the second slurry droplets were air-dried (step S2-4) to obtain an active material composite. The supply air temperature in the spray dryer was 200°C, and the supply air volume was 0.45 m. 3 / min, and the liquid delivery rate was 0.5 g / sec.
[0053] 3.Analysis of active material composites The surface elemental analysis of the above active material composite was carried out by X-ray photoelectron spectroscopy (XPS: PHI X-tool, ULVAC-PHI). The pass energy was set to 224 eV, and narrow scan analysis was carried out. The elemental ratios Li / P and F / P were calculated from the intensity values of each of the detected Li1s, C1s, O1s, F1s, P1s, Mn2p3, Co2p3, and Ni2p3 using the analysis software MultiPak (ULVAC-PHI). In addition, CF x The presence or absence of peaks due to
[0054] In addition, the appearance and cross-section of the above active material composites were observed to confirm the coverage and thickness of the coating layer in the active material composite. The coverage was nearly 100% and the thickness was approximately 20 nm for both the coating layers in the examples and comparative examples.
[0055] 4. Battery Construction and Evaluation 4.1 Preparation of the positive electrode Each active material composite of the examples and comparative examples and a sulfide solid electrolyte (10LiI-15LiBr-37.5Li3PS4) were weighed out to a volume ratio of 6:4, and these were put into heptane together with 3 mass% of vapor grown carbon fiber (VGCF) (manufactured by Showa Denko K.K.) as a conductive additive and 0.7 mass% of butadiene rubber (manufactured by JSR Corporation) as a binder. These were then mixed to prepare a positive electrode mixture. The prepared positive electrode mixture was thoroughly dispersed using an ultrasonic homogenizer, and then coated on aluminum foil and dried at 100°C for 30 minutes. After that, 1 cm 2 By punching out pieces of the same size, positive electrodes according to the examples and comparative examples were obtained.
[0056] 4.2 Preparation of the negative electrode A negative electrode active material (layered carbon) and a sulfide solid electrolyte (10LiI-15LiBr-37.5Li3PS4) were prepared in a volume ratio of 6:4, and these were put into heptane together with 1.2 mass% of butadiene rubber (manufactured by JSR Corporation) as a binder. Next, these were mixed to prepare a negative electrode mixture. The prepared negative electrode mixture was thoroughly dispersed using an ultrasonic homogenizer, and then coated on copper foil and dried at 100°C for 30 minutes. Then, 1 cm 2 A negative electrode was obtained by punching out a piece of the material having a size of 10 mm.
[0057] 4.3 Preparation of solid electrolyte layer Inner diameter cross-sectional area 1cm 2 64.8 mg of sulfide solid electrolyte (10LiI-15LiBr-37.5Li3PS4) was placed in the cylindrical ceramic, smoothed, and then pressed at 1 ton to form a solid electrolyte layer.
[0058] 4.4 Battery Construction The positive electrode prepared above was placed on one side of the solid electrolyte layer, and the negative electrode prepared above was placed on the other side, and pressed at 4.3 tons for 1 minute. Then, a stainless steel rod was inserted into both electrodes and restrained at 1 ton to obtain lithium ion secondary batteries according to each of the examples and comparative examples.
[0059] 4.5 Durability test The lithium ion secondary battery prepared as described above was subjected to a cycle test (voltage range 2.5 V to 4.4 V, 100 cycles) in a thermostatic chamber at 60° C. The resistance was measured at 3.66 V before and after the cycle test, and the resistance increase rate was calculated.
[0060] 5.Results The evaluation results are shown in Table 1 below.
[0061] [Table 1]
[0062] As is clear from the results shown in Table 1, the coating layers of the active material composites according to Examples 1 to 6 contain a phosphate compound, and C and F are introduced on the surface and / or inside. On the other hand, the coating layers of the active material composites according to Comparative Examples 1 to 3 contain a phosphate compound but do not contain C and F. As is clear from the results shown in Table 1, the active material composites according to Examples 1 to 6 have a smaller resistance increase rate after cycle testing and are more durable than the active material composites according to Comparative Examples 1 to 3. When the coating layer of the active material composite contains C and F together with the phosphate compound, the coating layer is less likely to decompose even at a high potential, which is thought to lead to improved durability. In addition, the presence of NaF was confirmed by XPS in some examples, but this is thought to be due to the reaction of Na contained as an excipient in the phosphoric acid with F.
[0063] In the above examples, positive electrode active material particles having a specific composition are exemplified, but the composition of the active material particles is not limited to this. In the above examples, LPO, BPO, and LBPO are exemplified as phosphate compounds, but the type of phosphate compound is not limited to this. However, it is considered that a higher effect can be obtained when the coating layer contains at least one of LPO, BPO, and LBPO. In the above examples, perfluoropolyether is exemplified as the C and F source, but the type of C and F source is not limited to this. However, it is considered that a higher effect can be obtained when the C and F contained in the coating layer are derived from perfluoropolyether.
[0064] From the above results, it can be said that the active material composite having the following configurations (1) to (4) has excellent durability after the cycle test. (1) The active material composite has active material particles and a coating layer. (2) The coating layer covers at least a portion of the surface of the active material particles. (3) The coating layer contains a phosphate compound. (4) The elements constituting the coating layer include C and F. [Explanation of symbols]
[0065] 1 Active material composite 1a Active material particles 1b Covering layer 100 Secondary battery 10 Positive electrode current collector 20 Cathode active material layer 30 Electrolyte layer 40 Negative electrode active material layer 50 Negative electrode current collector
Claims
1. An active material composite having active material particles and a coating layer, the coating layer covers at least a part of the surface of the active material particle, the coating layer contains a phosphate compound and NaF; The elements constituting the coating layer include C and F, The coating layer has a C—F bond derived from a perfluoropolyether. Active material complex.
2. 2. The active material composite according to claim 1 , The phosphate compound contains one or both of Li and B; Active material complex.
3. A secondary battery having a positive electrode active material layer, an electrolyte layer, and a negative electrode active material layer, The positive electrode active material layer comprises the active material composite according to claim 1 or 2. Secondary battery.
Citation Information
Patent Citations
Cathode active substance material, cathode active substance layer, all-solid battery, and method for producing cathode active substance material
JP2012099323A
Positive electrode active material for secondary battery, positive electrode for secondary battery, and method for manufacturing secondary battery
JP2013020899A
Method for manufacturing electrode material
JP2015228290A
Positive electrode active substance material for solid electrolyte-containing battery, and solid electrolyte-containing battery
JP2022011986A
Positive electrode active material for all-solid-state lithium secondary batteries
WO2019035418A1